High-performance polymer field-effect transistors: from the perspective of multi-level microstructures - Yao, Ze-Fan; Wang, Jie-Yu; Pei, Jian (Chemical science (Cambridge), 2020)
The multi-level microstructure of conjugated polymers is the most critical parameter determining the charge transport property in field-effect transistors (FETs). However, controlling the hierarchical microstructures and the structural evolution remains a significant challenge. In this perspective, we discuss the key aspects of multi-level microstructures of conjugated polymers towards high-performance FETs. We highlight the recent progress in the molecular structures, solution-state aggregation, and polymer crystal structures, representing the multi-level microstructures of conjugated polymers. By tuning polymer hierarchical microstructures, we attempt to provide several guidelines for developing high-performance polymer FETs and polymer electronics. The multi-level microstructures of conjugated polymers, including solution-state aggregation and crystal structures, are reviewed due to their influence on charge transport in polymer field-effect transistors.